1984
DOI: 10.1021/jm00376a003
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen bridgehead compounds. 44. New antiallergic 4H-pyrido[1,2-a]pyrimidin-4-ones. 4

Abstract: The weak antiallergic activity of 6-methyl-4-oxo-6,7,8,9-tetrahydro-4H-pyrido[1,2-a]pyrimidine-3-carbox yli c acid (1) in the rat reaginic passive cutaneous anaphylaxis test was enhanced by the introduction of an (arylamino)methylene moiety into position 9 of the pyridopyrimidine ring. Compound 34, (+)-6(S)-methyl-9-[(m-methylphenyl)-hydrazono]-4-oxo-4H-pyrido[1,2 -a] pyrimidine-3-carboxylic acid, displayed about 10 000 times the activity of the starting compound 1. A structure-activity relationship study of 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…It was reported that such tautomeric forms were observed in the synthesis of compounds 1a and 1b [22]. This situation was also previously observed for synthesis of pyridopyrimidine derivatives [23][24][25][26]. For compounds 1-6, there are even further tautomeric forms that are formed between C 2 -C 4 and at C 3 and the imine formed with the amino acids (scheme 2).…”
Section: Discussionsupporting
confidence: 72%
“…It was reported that such tautomeric forms were observed in the synthesis of compounds 1a and 1b [22]. This situation was also previously observed for synthesis of pyridopyrimidine derivatives [23][24][25][26]. For compounds 1-6, there are even further tautomeric forms that are formed between C 2 -C 4 and at C 3 and the imine formed with the amino acids (scheme 2).…”
Section: Discussionsupporting
confidence: 72%
“…Recently, the pyrido[2,3‐ d ]pyrimidine derivatives have received considerable attention because of their biological and pharmacological activities such as anti‐AIDS , antifungal , antileishmanial , tuberculostatic , antimicrobial , antitumor , tyrosin ekinase , anti‐inflammatory , antiallergic , analgesic , antibronchitic , hepatoprotective , antihypertensive , calcium channel antagonists , and antibacterial .…”
Section: Introductionmentioning
confidence: 99%
“…Uracil and its derivatives, such as pyrido [2,3-d]pyrimidines, have received considerable attention over the past years because of their biological activities, such as dihydrofolate reductase inhibiting, 1 antibacterial, 2 antiallergic, 3 antimicrobial, 4 tyrosine kinase inhibiting, 5 anti-inflammatory, 6 analgesic, 7 calcium channel antagonists, 8 antihypertensive, 9 antitubercular, 10 antileishmanial 11 and antifungal. 12 Several synthetic methodologies for the synthesis of 7-aminopyrido[2,3-d]pyrimidine-6-carbonitrile derivatives have been reported.…”
Section: Introductionmentioning
confidence: 99%